Epidemiology and Outcomes of Neonatal Hemophagocytic Lymphohistiocytosis - Balakumar, Niveditha; Sendi, Prithvi; Totapally, Balagangadhar R. (Frontiers in Pediatrics, 2022)
Objectives: Neonatal hemophagocytic lymphohistiocytosis (HLH) is a rare entity and needs a high index of suspicion for timely diagnosis and management. The objective of the study is to describe the prevalence, clinical characteristics, ICU interventions and outcomes of neonates diagnosed with HLH in the United States. Methods: A retrospective analysis on the Healthcare Cost and Utilization 2009, 2012 and 2016 Kids’ Inpatient Database was performed. Neonates admitted with the diagnosis of HLH were identified. Demographic and clinical characteristics, interventions and outcome variables were extracted and analyzed. Results: Among 11,130,055 neonatal discharges, 76 neonates had a diagnosis of HLH. Males comprised of 52% (95% CI: 38.6 - 63.6) and 54% (95% CI: 39.7 - 68.5) were white. Herpes simplex virus was present in 16% (95% CI: 9.2 -28.1). Bone marrow biopsy was documented in 33% (95% CI: 21.2-47.7), 24.4% (95% CI: 14.5 -37.9) of children received chemotherapy, 11.5% (95% CI: 5.2 -23.6) received IVIG and 3.6% (95% CI:0.8 -14.4) received allogenic hemopoietic stem cell transplantation. Organ dysfunction was commonly seen, and severe sepsis was documented in 26.6% (95% CI: 16.4 - 39.9). ECMO support was required in 3.7% (95% CI: 0.9- 14.6). Median LOS was 16 (IQR 7-54) days. The mortality was 42% (95% CI: 30.8-55). Conclusion: Although HLH is a rare diagnosis in neonates, it carries a high mortality. Herpes simplex virus is the most common infection associated with neonatal HLH. Clinicians should consider HLH in the differential diagnosis in neonates presenting with multi-organ dysfunction or sepsis.